Design and simulation of a multihoming-based inter-system handoff scheme in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina; Hasan, Mohammad Kamrul (Kaunas University of Technology, 2016)
Network mobility is an innovative concept for conducting a set of mobile nodes within a car-based mobile network. With the expanding wireless technology and increasing demands for ubiquitous Internet connectivity, mobile network is becoming more demanding technology. As a result, network mobility basic support protocol has been proposed by the internet engineering task force for the continual worldwide connectivity of each node within the mobile network. However, applying the multihoming technique in mobile network has become a considerable challenge due to rising traffic load resulting in extra handoff delay during inter system handoff of mobile router in network mobility. Multiple care of address registration mechanism among mobile routers along with its home agent has already been standardized to resolve some of the multihoming issues of network mobility. Yet a flow-based routing mechanism is still needed to support the mobility management in network mobility. Therefore, with the intent of reducing handoff delay, a novel multihoming-based inter-system handoff scheme on proxy mobile IPv6 domain in network mobility is proposed in this paper. Besides, the performance is evaluated through a simulation approach to validate the applicability and efficiency of the proposed scheme.